Role of New Hydrophilic Surfaces on Early Success Rate and Implant Stability: 1-Year Post-loading Results of a Multicenter, Split-Mouth, Randomized Controlled Trial - Tallarico, Marco; Baldini, Nicola; Gatti, Fulvio; Martinolli, Matteo; Xhanari, Erta; Meloni, Silvio Mario; Gabriele, Cervino; Immacolata, Lumbau Aurea (European Journal of Dentistry, 2020)
Objective To compare early implant failure and implant stability of one-stage Hiossen ET III implants with its new hydrophilic (NH) surface, compared with Hiossen ET III implants with the sandblasted and acid-etched (SA) surface at 1-year follow-up.Materials and Methods This study was designed as a split-mouth, multicenter randomized controlled trial aimed to compare SA surface implants (SA group) and NH surface, (NH group). Outcomes were implant and prosthetic survival rates, complications, the insertion torque at implant placement, and implant stability quotient (ISQ) values.Results Twenty-nine patients (mean age 59.9 ± 11.3 years) were treated and followed up to 1 year after loading. No patient dropped out. Fifty-eight implants (29 SA group and 29 NH group) were placed. No implants or prostheses failed and no complications were experienced during follow-up. The mean insertion torque was 40.5 ± 3.23 (38.17–41.83) Ncm in the SA group and 40.48 ± 3.49 (38.02–41.98) Ncm in the NH group (p = 0.981). There was a statistically significant difference at the second week (T2) with higher values in the NH group (p = 0.041). Similar results were found in the maxilla (p = 0.045), but not in the mandible (p = 0.362). A positive correlation was found between initial insertion torque and ISQ with higher value in the NH group (0.73 vs. 0.66).Conclusions NH implants are a viable alternative to SA surface, as they seem to avoid the ISQ drop during the bone remodeling phase.
Keywords: dental implants; implant surface; osseointegration; bone quality